Membangun Nasionalisme Melalui Pembelajaran Aswaja (Studi Kasus Siswa MAN Surabaya) - Ikwan, Mochamad; Wahyudi, Agus; Romdloni, M. Afwan (Penerbit STKIP PGRI Bangkalan, 2021)
The implications of the development of the industrial revolution era with society 5.0 have penetrated everything that has an impact on the fading of the spirit of nationalism. This research applies to describe how learning aswaja from the conceptual level to the realm of praxis where it is in the atmosphere of Nahdliyin as a tradition and technology through Aswaja Learning in an effort to build a spirit of nationalism in MAN Surabaya students. By using qualitative methods in hopes of providing a description of a phenomenon based on empirical reality. This study produces an overview with Aswaja learning materials given to students at MAN Surabaya to build students' spirit of nationalism. The parameters of the spirit of nationalism that can be observed by students include (1) high religiosity of students, (2) tolerant attitude (3) union and honesty (4) chastisement (5) organized (6) courage and honesty (7) respect the hero (8) autonomous (9) accountability, and (10) love lokal indigineous.